E-Commerce on Fashion Business - Soegoto, Eddy Soeryanto; Badria, S G (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to identify developments and opportunities by using technology as well as the benefits of e-commerce on the fashion business. To support this research, this study used a descriptive method by describing the situation. The results of this study show the extent of technological developments and opportunities on the fashion business. This study also discusses the ease the use of e-commerce for sale fashion products that will be carried out by companies using e-commerce technology.